Global Networks Linked Cities - Sassen, Saskia (Routledge, 2002)
First published in 2002. Routledge is an imprint of Taylor & Francis, an informa company. Saskia Sassen , Professor of Sociology at the University of Chicago, is a leading expert on cities and globalizaiton. She has published numerous books, including The Global City (1991, 2000) Cities in a World Economy (1994), Globalization and its Discontents (1998), Losing Control? (1996), Guests and Aliens (1999), and The Mobility of Labor and Capital (1988).